A 15,800-year record of atmospheric lead deposition on the Devon Island Ice Cap, Nunavut, Canada: natural and anthropogenic enrichments, isotopic composition, and predominant sources - Zheng, Jiancheng; Shotyk, William; Krachler, Michael; Fisher, David A. (Global biogeochemical cycles, 2007)
Using appropriate clean methods for handling and preparation, 57 ice samples from the Devon Island Ice Cap, representing the period 134 to 15,800 years before present (BP), were analyzed for Pb, Sc, and Pb isotopes (206Pb, 207Pb, 208Pb) using ICP-SMS. The greatest Pb concentrations were found in samples dating from the Younger Dryas. Despite the large range in Pb concentrations (from 2.2 to 181 pg g−1), the Pb concentrations were proportional to those of Sc until 3100 BP when the Pb/Sc ratio exceeded by a factor of 2 the natural “background” value (Pb/Sc = 6.3 ± 1.8) for the first time. The uniform ratio of Pb to Sc until 3100 BP is consistent with the hypothesis that soil dust particles derived from physical and chemical weathering dominate the inputs of Pb to the atmosphere, with the magnitude of these sources climate-dependent. Isotopic analyses of Pb further support this paradigm, with the average ratio of 206Pb/207Pb (1.230) and 208Pb/206Pb (2.059) well within the range given for the Upper Continental Crust (UCC). The shift to higher Pb/Sc ratios and lower 206Pb/207Pb values starting at 3100 BP is consistent with historical records and other archival evidence of the onset of atmospheric Pb contamination caused by Pb mining and smelting in the Iberian Peninsula. Since that time, the Devon Island ice core records several other episodes of notable atmospheric Pb contamination, including those dating from Roman and medieval times, as well as the industrial period. The Pb, Sc, and Pb isotope data presented here represent the first chemical and isotopic record of the natural, “background” atmospheric inputs to the Canadian Arctic, against which modern values may be compared.
Gesehen am 28.09.2020